THE EFFECTIVENESS OF INTERACTIVE MEDIA BRAINSMART GAMES ON THE LOGICAL THINKING ABILITY OF CHILDREN AGED 5-6 YEARS - Fikri, Mohammad Tsaqibul; Soraya, Nadya Najma (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
the logical thinking abilities of children aged 5-6 years. Combining fun games with cognitive educational principles, brainsmart games offer activities that stimulate critical thinking and logic through challenges appropriate to a child's developmental stage. This journal is the result of experimental research with a pre-experimental design and involves two variables, namely the independent variable and the dependent variable, the independent variable is the interactive media brainsmart games and the dependent variable is the logical thinking ability of children aged 5-6 years at RA Miftahul Huda Gondang Bojonegoro. Data collection was carried out using observation, documentation and test techniques. Data analysis techniques include validity tests, normality tests and hypothesis tests to find out whether there are differences in the results of measuring children's logical thinking abilities. Based on the research conducted, the following results were obtained: (1) the use of interactive brainsmart games media can improve the logical thinking abilities of children aged 5-6 years (2) the interactive media brainsmart games is effective for improving logical thinking abilities in children aged 5-6 years. The results of research and data analysis show that the average PreTest score is 13.45, which is lower than the Post Test score, namely 19.75. Meanwhile, the results of hypothesis testing using the paired sample T-test revealed the sig value. (2-tailed) of 0.000. From the increase in learning outcomes, it can be concluded that the games are effective in improving the logical thinking abilities of children aged 5-6 years.